2004
DOI: 10.1166/jnn.2004.120
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Silica Nanoparticles as Gene Carriers: Synthesis, Characterization and Transfection Efficiency <I>In vitro</I> and <I>In vivo</I>

Abstract: The potential of cationic SiO2 nanoparticles was investigated for in vivo gene transfer in this study. Cationic SiO2 nanoparticles with surface modification were generated using amino-hexyl-amino-propyltri-methoxysilane (AHAPS). The zeta potential of the nanoparticles at pH = 7.4 varied from -31.4 mV (unmodified particles; 10 nm) to +9.6 mV (modified by AHAPS). Complete immobilization of DNA at the nanoparticle surface was achieved at a particle ratio of 80 (w/w nanoparticle/DNA ratio). The surface modified na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(64 citation statements)
references
References 0 publications
3
56
0
1
Order By: Relevance
“…Some researchers have reported that SiNPs that carry a positive charge are more likely to function as DNA carriers for gene transfection. 22,23) In the present study, the potential zeta value of SiNPs was −12.76 mV, and they entered into alveolar macrophages through nonspecific phagocytosis. We assume that SiNPs of positive charge may have different affinity for cell membranes to that of negatively charged SiNPs, so the toxicity between differently charged nanoparticles would also be different.…”
Section: Discussionsupporting
confidence: 45%
“…Some researchers have reported that SiNPs that carry a positive charge are more likely to function as DNA carriers for gene transfection. 22,23) In the present study, the potential zeta value of SiNPs was −12.76 mV, and they entered into alveolar macrophages through nonspecific phagocytosis. We assume that SiNPs of positive charge may have different affinity for cell membranes to that of negatively charged SiNPs, so the toxicity between differently charged nanoparticles would also be different.…”
Section: Discussionsupporting
confidence: 45%
“…Moreover, it was found that cationic SiO 2 nanocomposites functionalized with amino-hexylamino-propyltrimethysilane exhibited no or very low cytotoxicity (De Jong & Borm, 2008). As can be noticed, no conclusive results have been reported, though, since they have been proved to be both toxic (Chang et al, 2007) and non-toxic (Ravi Kumar et al, 2004).…”
Section: Toxicity Evaluation and Existing Datamentioning
confidence: 99%
“…24 Investigations were performed to encapsulate DNA-cation-complexes into microspheres, but the preparation is complicated and yields microscaled particles. 25 Successful transfection in vitro and in vivo has been achieved with positively charged silica nanoparticles; 21,26 however, the fate of the inorganic carrier substance silica may remain a problem. In order to address this issue it was decided to develop nanoparticulate DNA carriers based on biodegradable polymers.…”
Section: Introductionmentioning
confidence: 99%